The Effect of Grain Position on Genetic Improvement of Grain Number and Thousand Grain Weight in Winter Wheat in North China - Feng, Fan; Han, Yunliang; Wang, Shengnan; Yin, Shaojing; Peng, Zhenyu; Zhou, Min; Gao, Wenqi; Wen, Xiaoxia; Qin, Xiaoliang; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2018)
Genetic improvements have significantly contributed to wheat production. Five wheat cultivars—widely grown in north China in the 1950s, 1990s, or 2010s—were grown in field experiments conducted in the 2014–2015 and 2015–2016 growing seasons. This study evaluated the genetic progress in wheat grain yield and its related traits in north China and explored how breeding and selection have influenced grain numbers and weights within spikelets in the past 60 years. The results showed that the significant increases in grain yield in the past 60 years were mainly due to increases in grain number per spike and grain weight, while spike number per m2 has not changed significantly. Improvements in thousand grain weight (TGW) from the 1950s to 2010s have occurred at four grain positions (G1 to G4). The relative contribution of G4 to TGW increased over time, but was much less than the contributions of G1, G2, and G3. Indeed, the average grain weight at G4 was much less than that of 1000 grains. The increase in grain number per spike since the 1950s was mainly due to an increase in grain number at G1, G2 and G3, with the relative contribution of grain position to grain number being G1 > G2 > G3 > G4. Dwarfing genes increased grain number per spike and grain number at G3 and G4, but not TGW. In future, yields could be boosted by enhancing grain weight at G4 and grain number at G3 and G4, while maintaining those at G1 and G2.